Partisipasi Masyarakat Nagari Pariangan dalam Pemberdayaan Desa Wisata Alam dan Budaya - Desliani, Silvia; Amertha, Mohammad Fajar (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2021)
Background. Nagari Tuo Pariangan is a village located in Pariangan sub-district, Tanah Datar Regency, West Sumatra Province. In the Minangkabau Tambo it is stated that Nagari Tuo Pariangan is the oldest village in Minang land as well as the forerunner to the establishment of other villages in West Sumatra. Their source of income is from farming and gardening and the community is quite prosperous and part of the population migrates. With the natural wealth of the people of Nagari Tuo Pariangan, they also empower their area as a leading tourism and culture, this is proven by the 2014 statistical increase of 511 foreign tourists, 5651 archipelago, 2015, 625 foreign tourists; 7253 archipelago, 2016 936 foreign countries, 17,836 archipelago. This development shows that the level of community participation in Nagari Tuo Pariangan has increased participation and has also experienced developments in other sectors, such as the development sector of economic life, and the social sector in the community. From a level that only relies on rice fields and plantations, it has increased with an increase in the tourism sector.Aim. Describe the level of participation of the Nagari Parianagan Community in Empowerment as a Natural and Cultural Tourism Village.Methods. To conduct this research, the methodology used is qualitative by exploring all sources of library data for research. Results.The results of the study show that the level of community participation in Nagari Tuo Pariangan has increased, especially in the form of partnerships, resulting in increased community empowerment in the Natural and Cultural Tourism Village.